LPP is a Src substrate required for invadopodia formation and efficient breast cancer lung metastasis - Elaine Ngan (Nature Portfolio, 2017)
Lipoma preferred partner (LPP) mediates TGFβ-induced breast cancer cell migration and invasion. Here the authors show that LPP is a Src-family kinase substrate that regulates the formation of protrusions of the plasma membrane -called invadopodia- required for breast cancer metastasis.